Synthetic approaches to 6-aryl-4-(2-furyl)methylidene-1-(tosylaminocarbonyl)-1,2,3,4-tetrahydropy rida zines-3-ones and 5-1-aroylmethyl-2-(2-furyl)-1-ethenyl-2-(tosylamino)-1,3,4-oxadiazoles - Hamad, Abdel-Sattar S. (Acta chimica slovenica, 2001)
Novel of 6-aryl-4-(2-furyl)methylidene-1-(tosylaminocarbonyl)-1,2,3,4-tetrahydropyrida zine-3-ones 4a-d were prepared by the reaction of ?$α-acryl-β-(2-fury)acrylic$? acid hydrazindes 2a-d with tosylisocyanate. This has been shown to occur by initial formation of ?$N^1-aroylmethyl-3-(2-fury)acroyloy-N^2-(tosylaminocarbonyl)hydrazines$? 3a-d followed by acid catalyzed cyclization to afford 5-1-aroylmethyl-2-(2-furyl)-1-ethenyl-2-(tosylamino)-1,3,4-oxadiazoles 5a-d.
Keywords: furanoni; heterociklične spojine; heterociklični sistemi; oksadiazoli; piridazini; piridazinoni; sinteza; struktura